Gamma-aminobutyric acid (GABA) and acetylcholine (ACh) alleviate water deficit effects in soybean: From gene expression up to growth performance - Braga-Reis, Inae [UNESP]; Neris, Daniel Moreira; Ribas, Alessandra Ferreira; Esteves Vieira, Luiz Gonzaga; Souza, Gustavo Maia (Elsevier B.V., 2021)
Bioregulators act as priming agents under abiotic stress conditions. Bioregulators such as gamma-aminobutyric acid (GABA) and acetylcholine (ACh) affect the efficiency of the antioxidant system and the regulation of the stomatal aperture, respectively. The aim of this study was to verify a possible synergistic effect among these bioregulators as attenuators of the effects of water deficiency in Glycine max. We combined the application of GABA and ACh at 2.0 mM in soybean plants under different water regimes. The factors studied were: 1) application of Gaba and ACh in seeds (S); in leaves (L); in seeds and leaves (SL); control without application (C); and (2) water regimes at 100 % field capacity (FC) and water deficit (WD). When the application of bioregulators were removed from the process, a severe decrease in photosynthesis capacity (93 %) was observed on the sixth day (after withholding water), as well as a higher expression of the genes known to be induced by water deficit. The combination of GABA and ACh applied to seeds and leaves under water deficit resulted in a lower decline in photosynthesis, as well as better water-use efficiency and biomass production. Soybean plants subjected to this treatment also showed lower expression of GmABA2, GmLEA3 and GmP5CS genes, lower proline content and increased activity of SOD, CAT and APX compared to the control treatment. The results indicate that the combined exogenous application of GABA and ACh in soybean plants acted to promote increased tolerance to water deficit, showing their potential for use on agricultural areas which are prone to droughts.
Keywords: Abiotic stress; Bioregulators; Glycine max; Priming; Water deficit